MicroRNA‐487a‐3p functions as a new tumor suppressor in prostate cancer by targeting CCND1. Issue 2 (15th July 2019) - Wang, Mingming; Yu, Wanpeng; Gao, Jun; Ma, Wenqiang; Frentsch, Macro; Thiel, Andreas; Liu, Mei; Rahman, Nafis; Qin, Zhihai; Li, Xiangdong
Abstract: Prostate cancer (PCa) is one of the major health problems of the aging male. The roles of dysregulated microRNAs in PCa remain unclear. In this study, we mined the public published data and found that miR‐487a‐3p was significantly downregulated in 38 pairs of clinical prostate tumor tissues compared with the normal tissues. We further verified this result by in situ hybridization on tissue chip and quantitative real‐time polymerase chain reaction (qRT‐PCR) in PCa/normal cells. miR‐487a‐3p targeting of cyclin D1 (CCND1) was identified using bioinformatics, qRT‐PCR and western blot analyses. The cellular proliferation, cell cycle, migration, and invasion were assessed by cell counting kit‐8, flow cytometry analysis and transwell assay. We discovered that overexpression of miR‐487a‐3p suppressed PCa cell growth, migration, invasion by directly targeting CCND1. Knockdown of CCND1 in PCa cells showed similar results. Meanwhile, the expression level of CCND1 was significantly upregulated in the PCa tissues and cell lines, which presented negative correlation with the expression of miR‐487a‐3p. More important, we demonstrated significantly reduced growth of xenograft tumors of stable miR‐487a‐3p‐overexpressed human PCa cells in nude mice. Taken together, for the first time, our results revealed that miR‐487a‐3p as a tumor suppressor of PCa could target CCND1. Our finding might reveal miR‐487a‐3p could be potentially contributed to the pathogenesis and a clinical biomarker or the new potential therapeutic target of PCa. Abstract : 1. miR‐487a‐3p was significantly downregulated in prostate tumor tissues and cell lines compared with the normals. 2. miR‐487a‐3p suppressed PCa cell growth, migration, invasion by directly targeting CCND1 in vitro and in vivo.